PENGARUH SISTEM AKUNTANSI MANAJEMEN DAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL SKPD DI KABUPATEN SIDENRENG RAPPANG - Haslindah Haslindah; Jeni Kamase; Hajering Hajering (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
In this study the author has the objective to determine the effect of management accounting system and budget particiaption on managerial performance on the staff of the Local Government Sidenreng Rappang either partially or simultaneously. The hypothesis of this study is: Suspected of management accounting system and budget particiaption have a significant impact on the performance of managerial staff of the Local Government Sidenreng Rappang either partially or simultaneously. Â The data required in this study is primary data in the form of respondentsâ€™ assessment of Management Accounting Systems, Budget Particiaption and Managerial Performance in Local Government Offices Sidenreng Rappang. Data collection methods used in this study is the questionnaire as well as a literature review on the books related to the subject matter covered. Data analysis techniques used by Multiple Linear Regression Test, t test, F test, Coefficient of Determination Test. The results of the data analysis in this study it can be concluded that the management accounting system and budget particiaption have a significant influence on the performance of managerial staff of the Local Government Sidenreng Rappang either partially or simultaneously.